Quality of Life Post Lympho-Venous Anastomosis in Breast Cancer–Related Lymphedema in the Indian Population - Marwah, Annika; Chandrappa, Ashok Basur; Vasudevan, Srikanth; Y.N, Ananteshwar; Jana, Aditya; Radadia, Jeet; Shetty, Pooja; B., Serena (Indian Journal of Plastic Surgery, 2025)
Secondary lymphedema negatively impacts the quality of life. Lympho-venous anastomosis (LVA) has shown to attenuate lymphedema symptoms.The aim of the study is to evaluate the efficacy, patient satisfaction, and quality of life following LVA for breast cancer–related lymphedema (BCRL) in the Indian setup.We conducted a prospective, nonrandomized, feasibility study at a single institute. Sixteen patients with BCRL undergoing secondary LVA between May 2020 and December 2021 were included in the study. Volumetry was done preoperatively and then 6, 12, and 18 months postoperatively. The Indian limb lymphedema scoring (ILLS) system questionnaire and satisfaction scoring were done 1 year postoperatively.Sixteen patients undergoing secondary LVA for BCRL were included in the study. The preoperative mean difference in limb circumference volume was 804.41 ± 472.01. This was reduced to 471.81 ± 292.216 mL at the 6-month follow-up (t = –6.6323; p ≤ 0.00001), 448.58 ± 255.93 (t = –5.5295; p = 0.00006) at 12 months, and 445.25 ± 345.78 (t = –6.8957; p ≤ 0.00001) at 18 months of follow-up. The mean volume difference between the two limbs at 12 months post-LVA was 515.3144 ± 284.2007 mL (t = 1.9972; p = 0.1250) and 362.7957 ± 201.9709 mL (t = 0.1221; p = 0.4522). The number of LVAs did not show a statistically significant difference in outcome with a volume difference of 515.3144 ± 284.2007 and 362.7957 ± 201.9709 mL in groups with less than four and more than four anastomosis and a p-value of 0.1250 and 0.4522, respectively. Similarly, body mass index (BMI) and duration of lymphedema did not show a statistically significant difference in outcome (p = 0.2648 and 0.2281, respectively). The mean total ILLS were 31.35 and 13.66 pre- and postoperatively, respectively, showing a statistically significant improvement in the quality of life, with a p-value of 0.00023.LVA significantly improves the quality of life and reduces limb volume, with stabilization occurring at 18 months, and the number of anastomoses, patient's BMI, and lymphedema duration did not affect volume reduction in our set of patients.
Keywords: lymphedema; breast cancer–related lymphedema; indocyanine green; lympho-venous anastomosis; Indian limb lymphedema scoring system